A case study: Analyzing the structure and optimizing the design of the aero handlebar assembly for the bicycle used in Japan's Olympic games - Sourav Das; Francesco Di Giuseppe; Antonio Flores; Sandhya Parate; Jaideep Bangal (Engineering Reports, 2024)
Abstract This article examines a case study involving a 3D‐printed titanium “aero base handlebar” that failed and caused a crash during the Japan 2020 Olympics. The failure was attributed to the handlebar's design, which did not meet the increasing demands of customers in terms of safety, cost, reliability, and comfort. The handlebar was created using in‐house Altair product tools like Inspire Studio, SIMSOLID, and SULIS. Static structural analysis was conducted by estimating boundary forces. The analysis revealed that the original handlebar design, with a width of 50 mm, did not meet the required safety standards. To address safety concerns, the article proposed moving the arms forward by 35 mm (1.37 in.) to create clearance and attempting to secure a modified aero handlebar with an 85 mm width. The modified design incorporated a lattice structure, which exhibited higher levels of deformation and stresses, as well as lower maximum fatigue damage compared to the original 50 mm design. These results highlight the importance of considering customer expectations for safety, reliability, and comfort. Company Altair's advanced proprietary software, including Inspire Studio, SIMSOLID, and SULIS, in addition to employing lattice optimization methods, can support designers and engineers in fulfilling these requirements and creating products that are both safer and more reliable.